2019
DOI: 10.1175/jcli-d-18-0471.1
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Convectively Coupled Kelvin Waves on Multiscale Rainfall Variability over the South China Sea and Maritime Continent in December 2016

Abstract: We studied the scale interactions of the convectively coupled Kelvin waves (KWs) over the South China Sea (SCS) and Maritime Continent (MC) during December 2016. Three KWs were observed near the equator in this month while the Madden–Julian oscillation (MJO) was inactive. The impacts of these KWs on the rainfall variability of various time scales are diagnosed, including synoptic disturbances, diurnal cycle (DC), and the onset of the Australian monsoon. Four interaction events between the KWs and the westward-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Both Baranowski et al (2016) and Sakaeda et al (2020) respectively show that the diurnal cycle is intensified by Kelvin waves and Rossby waves, the latter especially over the ocean. Chen et al (2019) further emphasise the intensification of the diurnal cycle over land by Kelvin waves. Ferrett et al (2020) show that equatorial wave activity is linked to extreme rainfall in the region.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Both Baranowski et al (2016) and Sakaeda et al (2020) respectively show that the diurnal cycle is intensified by Kelvin waves and Rossby waves, the latter especially over the ocean. Chen et al (2019) further emphasise the intensification of the diurnal cycle over land by Kelvin waves. Ferrett et al (2020) show that equatorial wave activity is linked to extreme rainfall in the region.…”
Section: Introductionmentioning
confidence: 94%
“…Chen et al . (2019) further emphasise the intensification of the diurnal cycle over land by Kelvin waves.…”
Section: Introductionmentioning
confidence: 99%
“…Convectively coupled Kelvin waves (KWs) are a dominant force in tropical subseasonal precipitation variability (Murata et al 2006;Wang and Fu 2007;Sinclaire et al 2015;Chen et al 2019;Latos et al 2021). These waves exert significant influence on global weather extremes and climate variability across multiple scales (Flatau et al 2003;Bessafi and Wheeler 2006;Straub et al 2006;Roundy 2008;Lawton and Majumdar 2023;Cheng et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show a considerable variance of tropical convection is found to be controlled by convectively coupled equatorial waves (Roundy and Frank, 2004;Kiladis et al, 2009). In the MC, for instance, the convectively coupled Kelvin waves in the lower level of the troposphere have an important impact on rainfall variability in the MC (Chen et al, 2019). Ferrett et al (2020) show various extreme rainfall events in southeast Asia are linked to various modes of the equatorial wave.…”
Section: Introductionmentioning
confidence: 99%